Struktur modal Sebagai Faktor Mediasi: Studi Empiris pada Perusahaan-Perusahaan Sub-Sektor Farmasi yang Listing di Bursa Efek Indonesia Periode 2012-2022 - Rosliana Marten; Akhmadi Akhmadi (Tirtayasa Ekonomika, 2025)
This research aims to empirically test the influence of profitability and liquidity on company value with capital structure as an intervening variable. Using 6 company samples from 11 companies in the Pharmaceutical Sub-Sector listed on the Indonesian Stock Exchange. The research sample was determined using a purposive sampling technique. The observation period is 2012-2021, so the research used 60 observational data. Data analysis in this study used descriptive statistics, multivariate linear regression, and hypothesis testing. The research results prove that liquidity has a positive and significant effect on company value. Liquidity has a negative and significant effect on capital structure. However, capital structure cannot mediate the effect of liquidity on company value.